Diagnostic accuracy of Ara h 2 for detecting peanut allergy in children. Issue 8 (29th July 2021) - Kansen, Hannah M.; van Erp, Francine C.; Meijer, Yolanda; Gorissen, Dianne M.W.; Stadermann, Marike; van Velzen, Maartje F.; Keusters, Willem R.; Frederix, Geert W.J.; Knulst, André C.; van der, Cornelis K.; Le, Thuy‐My
Abstract: Background: Specific IgE to Ara h 2 is a diagnostic test for peanut allergy which may reduce the need for double‐blind placebo‐controlled food challenges (DBPCFC); however, guidance for using Ara h 2 in place of DBPCFCs has not been validated. Objective: To prospectively evaluate 1) diagnostic accuracy of previously published Ara h 2 cut‐off levels to diagnose peanut allergy in children and 2) costs. Methods: A consecutive series of 150 children age 3.5 to 18 years was evaluated in secondary and tertiary settings in the Netherlands. sIgE to Ara h 2 was the index test, and oral peanut ingestion was the reference test. Oral peanut ingestion was home or supervised introduction for Ara h 2 ≤ 0.1, DBPCFC for 0.1–5.0 and open food challenge for ≥5.0. Costs were calculated using financial healthcare data. Results: A conclusive reference test was performed in 113 children (75%). Sixty‐four children (57%) had peanut allergy, as confirmed by a DBPCFC (27/47) or an open challenge (37/50). Forty‐nine children (43%) were considered peanut‐tolerant after peanut introduction (19/19), a DBPCFC (20/47) or an open challenge (10/50). Area under the curve for Ara h 2 was 0.94 (95% CI 0.90–0.98). The diagnostic flow chart correctly classified 26/26 (100%; 84–100) of children with Ara h 2 ≤ 0.1 as peanut‐tolerant and 34/35 (97%; 83–100) of children with Ara h 2 ≥ 5.0 as peanut‐allergic. At a cut‐off of ≤0.1 and ≥5.0, a sensitivity of respectively 100% (93–100) and 53% (38–67) was observed and a specificity of 53% (38–67) and 98% (87–100). Mean annual costs of the flow chart were estimated as €320‐€636 per patient lower than following national allergy guidelines. Conclusions: In this diagnostic accuracy study, which did not take into account pretest probability, we have validated previously published Ara h 2 cut‐off levels which are associated with peanut tolerance and allergy. Abstract : In children with suspected allergy, the sIgE to Ara h 2 cut‐off levels to predict peanut tolerance (cut‐off of ≤0.1) and peanut allergy (cut‐off of ≥5.0) were validated.